Evaluation of stability and enhancement of nano fluid methods - Shaalan, Z. A.; Hussein, A. M.; Abdullah, M. Z.; Noor, M. M. (IOP Publishing, 2024)
Over the last ten years, there has been a substantial increase in research on nanofluids, and the findings indicate that these fluids are superior heat transfer fluids for application in engineering. The improved heat transfer is exclusively dependent on the thermal conductivity of the nanoparticles at constant particle volume concentrations and flow rates. By creating hybrid nanoparticles, one can change or vary the thermal conductivity of nanoparticles. Nanoscale particles with two or more separate components come together to form hybrid nanoparticles. Fluids made from hybrid nanoparticles are known as hybrid nanofluids. By utilizing more sophisticated materials, hybrid Nano fluids aim to significantly boost heat transmission. Results shows that the nanofluid stability is sensitive to environmental conditions including temperature, pH, and shear rate. It should be using surfactants, additives such as polymers and colloids, ultra-sonication, high shear mixing, applying magnetic field.